RETRACTED: Evaluation of Pt,Pd-Doped, NiO-Decorated, Single-Wall Carbon Nanotube-Ionic Liquid Carbon Paste Chemically Modified Electrode: An Ultrasensitive Anticancer Drug Sensor for the Determination of Daunorubicin in the Presence of Tamoxifen - Alizadeh, Marzieh; Azar, Parviz Aberoomand; Mozaffari, Sayed Ahmad; Karimi-Maleh, Hassan; Tamaddon, Ali-Mohammad (Frontiers in Chemistry, 2020)
Measuring the concentration of anticancer drugs in pharmacological and biological samples is a very useful solution to investigate the effectiveness of these drugs in the chemotherapy process. A Pt,Pd-doped, NiO-decorated SWCNTs (Pt,Pd-NiO/SWCNTs) nanocomposite was synthesized using a one-pot procedure and combining chemical precipitation and ultrasonic sonochemical methods and subsequently characterized by TEM and EDS analysis methods. The analyses results showed the high purity and good distribution of elements and the ~10-nm diameter of the Pt,Pd-NiO nanoparticle decorated on the surface of the SWCNTs with a diameter of about 20–30 nm. Using a combination of Pt,Pd-NiO/SWCNTs and 1-butyl-2,3-dimethylimidazolium tetrafluoroborate (1B23DTFB) in a carbon paste (CP) matrix, Pt,Pd-NiO/SWCNTs/1B23DTFB/CP was fabricated as a highly sensitive analytical tool for the electrochemical determination of daunorubicin in the concentration range of 0.008–350 μM with a detection limit of 3.0 nM. Compared to unmodified CP electrodes, the electro-oxidation process of daunorubicin has undergone significant improvements in current (about 9.8 times increasing in current) and potential (about 110 mV) decreasing in potential). It is noteworthy that the designed sensor can well measure daunorubicin in the presence of tamoxifen (two breast anticancer drugs with a ΔE = 315 mV. According to the real sample analysis data, the Pt,Pd-NiO/SWCNTs/1B23DTFB/CP has proved to be a promising methodology for the analysis and measuring of daunorubicin and tamoxifen in real (e.g., pharmaceutical) samples.